Principals Gender and the Utilization of Legal Provisions in Administration of Secondary Schools in Cross River State, Nigeria - Ekere, Scholastica C. O (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2021)
This study investigated the influence of principals` gender on the utilization of legal provisions in secondary school administration in cross river state, Nigeria. The sample consisted of four hundred and twenty six principals from both private and public secondary schools in cross river state. One hypothesis was formulated to guide they study. Ex-post facto design was adopted for the study. A sample size of 426 principals from public secondary schools, were drawn from a population of 780 principals using stratified random sampling technique. The instrument for data collection was a questionnaire titled “Principals utilization of legal provisions in secondary schools Administration Questionnaire (PULPSSAQ). The data collected were subjected to statistical analysis using independent t-test. The results of the data analyzed showed that female principals utilized legal provisions more than their counterparts’. The principals’ sex did not have any influence on staff administration and school community relation. It was concluded that sex of the principal was critical in some aspect of utilizations of legal provisions should be made for in service training, regular workshops and seminars for principals especially males to help upgrade their knowledge with modern techniques of utilizing legal provisions in secondary school administration.